Legal framework and structure of community mediation in Malaysia : a proposal - Hanna binti Ambaras Khan (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
Community mediation is an extremely beneficial programme that enables the people to solve their neighbourhood problems within the community, without the hassle of bringing the matter to court. Under the Department of National Unity and Integration (DNUI), Malaysia has initiated a community mediation programme, however, it is without a proper legal framework or organisational structure, hence the DNUI and the community mediators faced many challenges such as no governing law, proper place to conduct mediation sessions and lack of continuous training. Ho Kek Hwa (2009) highlights the challenges faced by the DNUI. A proper institutionalised community mediation would, on the other, ensure effectiveness of the programme besides offering many other advantages to the nation. Thus, to streamline the practice of community mediators in Malaysia, a legal framework and a proper organisational structure of an institutionalised community mediation programme is necessary. One of the objectives of this study is to examine the current practice of community mediation in East and West Malaysia, Singapore and Kerala, India. Major part of the study is focused towards the proposal of a legal framework and organisational structure of community mediation in Malaysia with the intention to institutionalise the programme. A qualitative legal research has been conducted on the current practice of community mediation in Malaysia, Singapore and India. A hundred and seventy five (175) respondents comprising of directors and officers of DNUI, judges of high court and native courts, Penghulu (headman), professional mediators, community mediators and Rukun Tetangga (Peaceful Neighbourhood) committee members were interviewed. The findings of this study reveal that the current community mediation programme needs to be revamped and regulated. This study further proposes a new Malaysian Community Mediation Act 2015. Overall, this study is a notable solution to the dispute solving mechanism in Malaysia and a significant contribution to the existing literature on community mediation in Malaysia.